Correction: Surface group modification and carrier transport properties of layered transition metal carbides (Ti2CTx, T: –OH, –F and –O). Issue 2 (9th December 2015) - Lai, Shen; Jeon, Jaeho; Jang, Sung Kyu; Xu, Jiao; Choi, Young Jin; Park, Jin-Hong; Hwang, Euyheon; Lee, Sungjoo
Abstract : Correction for 'Surface group modification and carrier transport properties of layered transition metal carbides (Ti2 CT x, T: –OH, –F and –O)' by Shen Lai, et al., Nanoscale, 2015, DOI: 10.1039/c5nr06513e.